Alterations in glycosylation as biomarkers for cancer detection. Issue 4 (30th March 2010) - Reis, Celso A; Osorio, Hugo; Silva, Luisa; Gomes, Catarina; David, Leonor
Abstract : Glycoconjugates constitute a major class of biomolecules which include glycoproteins, glycosphingolipids and proteoglycans. Glycans are involved in several physiological and pathological conditions, such as host–pathogen interactions, cell differentiation, migration, tumour invasion and metastisation, cell trafficking and signalling. Cancer is associated with glycosylation alterations in glycoproteins and glycolipids. This review describes various aspects of protein glycosylation with the focus on alterations associated with human cancer. The application of these glycosylation modifications as biomarkers for cancer detection in tumour tissues and serological assays is summarised.